Surviving and Thriving—Shifting the Public Health Response to HIV-Exposed Uninfected Children: Report of the 3rd HIV-Exposed Uninfected Child Workshop - Slogrove, Amy L.; Becquet, Renaud; Chadwick, Ellen G.; Côté, Hélène C. F.; Essajee, Shaffiq; Hazra, Rohan; Leroy, Valériane; Mahy, Mary; Murenga, Maurine; Wambui Mwangi, Jacqueline; Oyiengo, Laura; Rollins, Nigel; et al. (Frontiers in Pediatrics, 2018)
Great gains were achieved with the introduction of the United Nations’ Millennium Development Goals, including improved child survival. Transition to the Sustainable Development Goals (SDGs) focused on surviving, thriving and transforming, representing an important shift to a broader public health goal, the achievement of which holds the promise of longer-term individual and societal benefits. A similar shift is needed with respect to outcomes for infants born to women living with HIV (WLHIV). Programming to prevent vertical HIV transmission has been successful in increasingly achieving a goal of HIV-free survival for infants born to WLHIV. Unfortunately, HIV-exposed uninfected (HEU) children are not achieving comparable health and developmental outcomes compared with children born to HIV-uninfected women under similar socioeconomic circumstances. The 3rd HEU Child Workshop, held as a satellite session of the International AIDS Society’s 9th IAS Conference in Paris in July 2017, provided a venue to discuss HEU child health and development disparities. A summary of the Workshop proceedings follows, providing current scientific findings, emphasizing the gap in systems for long-term monitoring and highlighting the public health need to establish a strategic plan to better quantify the short and longer-term health and developmental outcomes of HEU children.